Association of asymptomatic spinal cord lesions and atrophy with disability 5 years after a clinically isolated syndrome. (April 2017) - Brownlee, WJ; Altmann, DR; Alves Da Mota, P; Swanton, JK; Miszkiel, KA; Wheeler-Kingshott, CAM Gandini; Ciccarelli, O; Miller, DH
Background: Spinal cord pathology is an important substrate for long-term disability in multiple sclerosis (MS). Objective: To investigate longitudinal changes in spinal cord lesions and atrophy in patients with a non-spinal clinically isolated syndrome (CIS), and how they relate to the development of disability. Methods: In all, 131 patients with a non-spinal CIS had brain and spinal cord imaging at the time of CIS and approximately 5 years later (median: 5.2 years, range: 3.0–7.9 years). Brain magnetic resonance imaging (MRI) measures consisted of T2-hyperintense and T1-hypointense lesion loads plus brain atrophy. Spinal cord MRI measures consisted of lesion number and the upper cervical cord cross-sectional area (UCCA). Disability was measured using the Expanded Disability Status Scale (EDSS). Multiple linear regression was used to identify independent predictors of disability after 5 years. Results: During follow-up, 93 (71%) patients were diagnosed with MS. Baseline spinal cord lesion number, change in cord lesion number and change in UCCA were independently associated with EDSS ( R 2  = 0.53) at follow-up. Including brain T2 lesion load and brain atrophy only modestly increased the predictive power of the model ( R 2  = 0.64). Conclusion: Asymptomatic spinal cord lesions and spinal cord atrophy contribute to the development of MS-related disability over the first 5 years after a non-spinal CIS.